Responsibility of education in improving medical college students’ ability to prevent and respond to public health emergencies in China – A systematic review - Fang, Xin; Zhao, Lei; Pang, Ran; Li, Huarong; Ye, Pian (Frontiers in Public Health, 2023)
Background The outbreak of coronavirus disease 2019 (COVID-19) has highlighted the critical importance of sufficient preparedness for public health emergencies. This places higher requirements on the ability of medical staff to deal with such emergencies. Nonetheless, education courses on public health emergencies in China are usually aimed at public health students, and not at all medical college students. Importantly, these medical students will become medical workers who are generally the first-contact personnel and play an irreplaceable role in responding to most public health emergencies. Therefore, it is urgent to strengthen educational courses to enable these students to adequately prevent and respond to public health emergencies. Objectives The purpose of this systematic review was to reveal the current unsatisfactory status of Chinese medical college students’ knowledge and skills in dealing with public health emergencies and their training needs. Methods We searched EMBASE, PubMed, Google Scholar, Web of Science, CNKI, Wan Fang, and VIP Information Network for all associated original studies written in English and Chinese from the inception of these databases until March 12, 2022. Results This systematic review screened out 15 eligible studies that met the inclusion criteria. These studies demonstrated that Chinese medical college students generally have a low ability to deal with public health emergencies. Most students believe it is essential to master coping with public health emergencies and desire to acquire this knowledge. But the participation rate is low, and only a few students actively seek relevant knowledge. Conclusion The findings of this review illustrate the importance of improving medical college students’ education to prevent and deal with public health emergencies. It is necessary to improve medical college students’ education in responding to public health emergencies. Systematic Review Registration: PROSPERO, Identifier [CRD42023467374].